PROFIL KINERJA GURU PENDIDIKAN JASMANI SD NEGERI - Triyono (LPPM Universitas Terbuka, 2014)
This study aims to determine the results of peer and student assessment of the performance of physical education teachers (Penjas) Elementary School in Purworejo, Banyuurip and Kutoarjo associated with pedagogical, professional, personal and social. This article only discusses the pedagogical competence of the physical education teacher. The study design was a survey with data collection by distributing questionnaires to colleagues and students. The population is the entire physical education teacher at the elementary school in the area Purworejo, Banyuurip and Kutoarjo with a sample of 200 teachers were taken by random sampling technique. Questionnaires were returned as many as 164 copies. The collected data were then analyzed by using percentages to facilitate exposure and describe in narrative. The results showed that most of the peers judge that pedagogical competence of teachers in elementary schools in Region Penjas Purworejo, Banyuurip and Kutoarjo is good (88%) or very good (29.2%). While students assess their pedagogical competence Penjas teachers with excellent 33.9%, 16.8% good and 14.8% is good enough. Penelitian ini bertujuan untuk mengetahui hasil penilaian teman sejawat dan siswa terhadap kinerja guru pendidikan jasmani (Penjas) SD Negeri di Kabupaten Purworejo, Banyuurip dan Kutoarjo terkait dengan kompetensi pedagogik, profesional, kepribadian dan sosial. Artikel ini hanya membahas kompetensi pedagogik dari guru penjas. Desain penelitian adalah survey dengan teknik pengumpulan data melalui penyebaran kuesioner kepada teman sejawat dan siswa. Populasi adalah seluruh guru penjas di SD di Wilayah Purworejo, Banyuurip dan Kutoarjo dengan sampel sebanyak 200 guru yang diambil dengan teknik random sampling. Kuesioner yang kembali sebanyak 164 eksemplar. Data yang terkumpul kemudian dianalisis dengan menggunakan teknik persentase untuk memudahkan pemaparan dan mendeskripsikannya secara naratif. Hasil penelitian menunjukkan bahwa hampir sebagian besar teman sejawat menilai bahwa kompetensi pedagogik guru Penjas di SD di Wilayah Purworejo, Banyuurip dan Kutoarjo sudah baik (88%) atau sangat baik (29,2%). Siswa menilai kompetensi pedagogik guru Penjas mereka dengan sangat baik 33,9%, baik 16,8% dan cukup baik 14,8 %.